Atualidade da Gaudium et Spes: o diálogo com um mundo em mudança - Manzini, Rosana (2009)
This academic research, as a master level work, aims to verify the present value of Pastoral Constitution Gaudium et Spes. It is due to the interest that Vatican Council II keeps causing, after so many years. The social-religious situation has changed. Therefore, a lucid and profound reanalysis is needed. In order to do so, using the theological method, we did a historical analysis of its antecedents, pointing the specific occasion in which this important document was published. Then, pointing out the document s guide-lines related to the recent Church Teaching announcements: Document of Aparecida (2007) and the Benedict XVI s Encyclic, Caritas in Veritate (2009). We have placed all these documents in its historical context, allowing the dialogue with Gaudium et Spes. The conclusion is that, after almost fifty years, Gaudium et Spes still fits nowadays reality and can be used as base to theological-pastoral reflection